Epitaxial Growth of CsPbX 3 (X = Cl, Br, I) Perovskite Quantum Dots via Surface Chemical Conversion of Cs 2 GeF 6 Double Perovskites: A Novel Strategy for the Formation of Leadless Hybrid Perovskite Phosphors with Enhanced Stability - Wei, Yi; Li, Kai; Cheng, Ziyong; Liu, Manman; Xiao, Hui; Dang, Peipei; Liang, Sisi; Wu, Zhijian; Lian, Hongzhou; Lin, Jun (Advanced materials (Weinheim), 2019)
Lead halide perovskites (LHPs) have received increased attention owing to their intriguing optoelectronic and photonic properties. However, the toxicity of lead and the lack of long‐term stability are potential obstacles for the application of LHPs. Herein, the epitaxial synthesis of CsPbX 3 (X = Cl, Br, I) perovskite quantum dots (QDs) by surface chemical conversion of Cs 2 GeF 6 double perovskites with PbX 2 (X = Cl, Br, I) is reported. The experimental results show that the surface of the Cs 2 GeF 6 double perovskites is partially converted into CsPbX 3 perovskite QDs and forms a CsPbX 3 /Cs 2 GeF 6 hybrid structure. The theoretical calculations reveal that the CsPbBr 3 conversion proceeds at the Cs 2 GeF 6 edge through sequential growth of multiple PbBr 6 4− layers. Through the conversion strategy, luminescent and color‐tunable CsPbX 3 QDs can be obtained, and these products present high stability against decomposition due to anchoring effects. Moreover, by partially converting red emissive Cs 2 GeF 6 :Mn 4+ to green emissive CsPbBr 3 , the CsPbBr 3 /Cs 2 GeF 6 :Mn 4+ hybrid can be employed as a low‐lead hybrid perovskite phosphor on blue LED chips to produce white light. The leadless CsPbX 3 /Cs 2 GeF 6 hybrid structure with stable photoluminescence opens new paths for the rational design of efficient emission phosphors and may stimulate the design of other functional CsPbX 3 /Cs‐containing hybrid structures.